Combined Feed Network for a Shared-Aperture Dual-Band Dual-Polarized Array - Vetharatnam, G.; Chung, Boon Kuan; Chuah, Hean Tiek (IEEE Xplore, 2005)
A new combined feed network is proposed for a shared-aperture dual-band dual-polarized array operating in the L/C band. The array comprises square, aperture-coupled patches in the C-band and a square perforated, aperture-coupled L-band patch. The feed networks of a single polarization for both the bands are combined into a single network on a single layer. Good return loss and radiation characteristics are obtained for L- and C-band frequencies.